2022
DOI: 10.3389/fchem.2022.870137
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Protonation Sites of 3-Styryl Derivatives of 7-(dialkylamino)-aza-coumarin Dyes Induced by Cucurbit[7]uril

Abstract: The incorporation of a guest, with different basic sites, into an organized system (host), such as macrocycles, could stabilize, detect, or promote the formation of a certain protomer. In this context, this work aimed to study the influence of cucurbit[7]uril (CB7) on dyes such as 7-(dimethylamino)-aza-coumarins, which have more than one basic site along their molecular structure. For this, three 3-styryl derivatives of 7-(dialkylamino)-aza-coumarin dyes (SAC1-3) were synthesized and characterized by NMR, ESI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Coumarins 1–11 are polyfunctionalized compounds that bear ether (coumarins 3 and 4 ) and ester functional groups and halogen atoms (coumarins 8 , 10 , and 11 ) that may be susceptible to protonation. Protonation at different sites of the coumarin structure produces different protonated regioisomers (i.e., species that differ only in the position at which the proton is attached), which are referred to in this study as “protomers.” 46,47 On the basis of gas‐phase basicity (GB) and proton affinities (PA), Bouchoux et al reported that the carbonyl oxygen is the most susceptible to protonation in the structure of polyfunctionalized molecules containing carbonyl groups or α,β‐unsaturated carbonyl groups 48,49 . Recently, by using DFT calculations, Sun et al demonstrated that the carbonyl oxygen is the most susceptible to protonation in the coumarin structure 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Coumarins 1–11 are polyfunctionalized compounds that bear ether (coumarins 3 and 4 ) and ester functional groups and halogen atoms (coumarins 8 , 10 , and 11 ) that may be susceptible to protonation. Protonation at different sites of the coumarin structure produces different protonated regioisomers (i.e., species that differ only in the position at which the proton is attached), which are referred to in this study as “protomers.” 46,47 On the basis of gas‐phase basicity (GB) and proton affinities (PA), Bouchoux et al reported that the carbonyl oxygen is the most susceptible to protonation in the structure of polyfunctionalized molecules containing carbonyl groups or α,β‐unsaturated carbonyl groups 48,49 . Recently, by using DFT calculations, Sun et al demonstrated that the carbonyl oxygen is the most susceptible to protonation in the coumarin structure 31 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, Alcázar et al. reported that the protonation site of an aza -coumarin dye could be altered via CB[7] complexation . Therefore, the observation and characterization of the protomers of multifunctional molecules in host–guest complexes must be conducted to understand the intrinsic recognition and captivation chemistries of targeted molecules.…”
Section: Introductionmentioning
confidence: 99%
“…coumarin derivatives (SACs), which bear two basic sites in their structure (Alcázar et al, 2022). They first synthesized three styrylderived SACs, namely SAC1, SAC2, and SAC3, which were fully characterized by HR ESI-MS, IR, and NMR.…”
mentioning
confidence: 99%
“…The complexation of a guest molecule with multiple basic sites and a macrocyclic host could stabilize, probe, or facilitate the formation of a specific protomer. To verify this, Alcázar et al investigated the impact of CB[7] on the synthetic dyes 7-(dialkylamino)-aza-coumarin derivatives (SACs), which bear two basic sites in their structure ( Alcázar et al, 2022 ). They first synthesized three styryl-derived SACs, namely SAC1 , SAC2 , and SAC3 , which were fully characterized by HR ESI-MS, IR, and NMR.…”
mentioning
confidence: 99%